Migration and health - Castañeda, Heide, author.
1 online resource (xiii, 166 pages).
Keywords: "Migration and Health offers a radical rethinking of the field by unsettling conventional ideas of mobility and borders to highlight the ways in which they produce health inequalities. It illustrates how a critical perspective can deepen our understanding of the relationship between migration and health"--